Facing Disruptive Challenges in Supply Chain 4.0 - Elfindah Princes (International Journal of Supply Chain Management, 2020)
Modern technology has set the business competition to a much higher level. With the increasing number of population all around the world, the proper supply chain management to ensure products availability is inevitably required. Modern Manufacturing industry must put in extra efforts in all fields, especially in the supply chain management system to make the products ready on time, at the right place, for designated customers. This will certainly be not easy because the world is changing continuously. Using qualitative research, this paper will discuss the disruptive challenges faced by modern manufacturing industry and the preparations need to be done by all parties included in Supply Chain 4.0. The findings show that Customer Experience will be the first brand differentiator in the future and must be given serious attention if we want to maintain firm performance.